Digital Generation: Are Manners Fading? Case Study at SDN 212 Harapan - Komara, Intan Budi; Muslimah, Revi; Septiany, Silvia; Leong, Celine Regita; Giwangsa, Sendi Fauzi (Widyagogik, 2024)
The digital generation has had a significant impact on various aspects of life, including education. Elementary school students, as a generation that is in the stage of cognitive and social development, are vulnerable to the negative impact of using digital media without supervision, one of which is the decline in manners. This study aims to analyse the factors that influence elementary school students' manners in the digital era and the efforts made by teachers in instilling these values. The research used a qualitative approach with a case study design. The results showed that digital media poses a big challenge to students' character building, especially good manners. However, character-based programmes such as the Pancasila Student Profile Strengthening Project (P5), the implementation of the 5S culture (smile, greeting, greeting, politeness, courtesy), and collaboration between schools and parents can have a positive influence in instilling the values of courtesy. The role of the teacher as the main role model in shaping student character is crucial. In addition, continuous evaluation of programme implementation is needed to ensure the success of character building. With a good synergy between schools, parents and students, the value of good manners can be maintained and strengthened despite the digital era.